Extraction and Purification of Terpenes from Nutmeg (myristica fragrans) - Al-Jumaily, Essam F; Al-Amiry, Maytham H A (Al-Nahrain Journal of Science, 2012)
This study was conducted with the aim to extract and purify the essential oil containing terpenes from the dried seeds of nutmeg myristica fragrans available in Iraqi markets.The essential oil was extracted by steam distillation method with a yield of 4.7 – 7.5 gm / 100 gm, and the resultant oil was subjected to sensory and physical evaluation. It has a special spicy odor, slightly pungent taste, colorless to pale yellow in color, not dissolved in water but dissolved in organic solvents like ethanol, hexane, chloroform and ether. The specific gravity, refractive index and optical rotation were (0.890 gm / ml), (1.4822) and (+22˚), respectively. Gas chromatography is used for the quality and quantity evaluation of the essential oil constituents which revealed the presence of 49 volatile compounds. The methanolic extract obtained by reflux the seeds powder with 70% methanol in soxhlet apparatus and yield 12.8%. The extract was subjected to phytochemical detection which confirms the presense of alkaloids, terpenes, flavonoids, glycosides, tannins and resins, with the exception of saponins and coumarines which gave negative tests. Myristicin was purified from the methanolic extract of nutmeg dried seeds, which were detected in the essential oil by TLC and vanillin-H2SO4 reagent. The purified myristicin was obtained after the application of adsorption chromatography on silica gel column and detected on T.L.C. plate with standard myristicin.Both the essential oil and purified myristicin were subjected to gas chromatography which showed the presence of myristicin in the oil in a concentration of 6%.